Effect of Transformational and Transactional Leadership Styles on Employee Performance and Its Impact on Quality of Work Life in Oil Processing Companies in Balikpapan - Gusti Noorlitaria Achmad; Fitriansyah Fitriansyah (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study aims to find out: 1) The Effect of Transformational Leadership Style on Employee Performance of oil processing companies in Balikpapan; 2) Effect of Transactional Leadership Style on Employee Performance of oil processing companies in Balikpapan; 3) Transformational Leadership Style on Quality of Work Life of oil processing companies in Balikpapan; 4) Effect of Transactional Leadership Style on Quality of Work Life of oil processing companies in Balikpapan. This research is a quantitative descriptive study with a total sample of 80 respondent nurses' employees. Data collection techniques using questionnaires and purposive sampling methods. Data analysis techniques in this study used Simple Linear Regression. The results showed the Transformational Leadership Style affects the Employee Performance of oil processing companies in Balikpapan(H1); the Transactional Leadership Style affects the Performance of Employees of oil processing companies in Balikpapan(H2). From these results, it can be concluded that all indicators have a positive and significant effect.